2015
DOI: 10.14800/rci.811
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Scavenger Receptors in the Safe Development of Nanotherapeutics

Abstract: Nanomaterials (NMs) are being utilized in a variety of biomedical applications including drug delivery, diagnostics, and therapeutic targeting. These applications are made possible due to the unique physicochemical properties that are exhibited at the nanoscale. To ensure safe development of NMs for clinical use, it is necessary to understand their interactions with cells and specifically cell surface receptors, which will facilitate either their toxicity and/or clinical function. Recently our research and oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…Through this pathway, nanoparticles are expected to accumulate in the cytoplasm, in agreement with what was observed in the Fig. 4A ( 48 ) . Other receptors, including the C-type lectin receptors (CLRs) and the mannose receptor (MR), can bind the fucose moieties of which fucoidan is composed.…”
Section: Resultssupporting
confidence: 88%
“…Through this pathway, nanoparticles are expected to accumulate in the cytoplasm, in agreement with what was observed in the Fig. 4A ( 48 ) . Other receptors, including the C-type lectin receptors (CLRs) and the mannose receptor (MR), can bind the fucose moieties of which fucoidan is composed.…”
Section: Resultssupporting
confidence: 88%
“…It has been widely reported that in physiologically relevant conditions, nanomaterials are mostly taken up the cell surface machinery through energy-driven processes, indicating the involvement of receptors in nanomaterial recognition. , Cell surface receptors typically expressed in monocytes and macrophages include Toll-like receptors (TLRs), Fc receptors (FcRs), and scavenger receptors (SRs) . While TLRs seem to play a role in the priming step, recent studies point toward the involvement of SRs in nanomaterials recognition in a variety of cell lines, suggesting a possible mediating role of SRs on silica nanoparticle uptake and triggering of the NLRP3 inflammasome activation cascade. , …”
mentioning
confidence: 99%
“…SR-A1 and CD36 are also PRR members and play a pivotal role in Aβ aggregation. Polystyrene-based and silver nanocarriers have been shown to interact with these receptors and inhibit microglial-mediated neuroinflammation [139]. Veglianese et al explored the role of PEG-conjugated nanocarriers in the delivery of minocycline across the BBB, demonstrating that these nanocarriers significantly inhibited microglial activation and reduced microglial activated neuroinflammation [140].…”
Section: Mechanism Of Nanocarriers For Targeting Microglial Activation In Admentioning
confidence: 99%